Predictors of knowledge sharing behaviour and mediating effect of self-efficacy among successful farmers in selected Malaysian states - Brooke, Jenefer (2016)
This study is to investigate the predictors of knowledge sharing behaviour and mediating variable of self-efficacy among successful farmers in selected Malaysian states. In Malaysian agriculture context, knowledge sharing behaviour of successful farmers formally and informally occurs during training, farm visits and also through discussions. However, current practices among farmers in the sharing process are unstructured and lack clarity. To date, there is no certain mechanism or coordination, which can be followed and properly implemented, leaving the issue unclear and unresolved. Hence, examining how individuals’ personal factors and environmental factors affect shape successful farmers’ knowledge sharing behaviour is imperative in order to formulates a strategy towards encouraging knowledge sharing culture in the agriculture community. Investigating this process is both theoretical and practically significant to provide better understanding of knowledge sharing behaviour among successful farmers. This study employed Social Cognitive Theory and Endres et al.’s (2007) model of knowledge sharing behaviour in order to provide an integrative theoretical framework in explaining knowledge sharing behaviour among successful farmers. Further, the present study aimed to examine the mediating role of self-efficacy on the relationship between independent variables (e.g., individual and environmental-related factors) and knowledge sharing behaviour among successful farmers. The findings indicated the level of knowledge sharing behaviour was high among 241 respondents of successful farmers. Subsequently, the result showed that successful farmers possessed high level of self-efficacy, enjoyment in helping others, perceived high level of training and prior experiences. Similarly, perceived social support and trust were also reported high among the successful farmers. The results in the PLS-SEM path models revealed that individual-related factors (enjoyment in helping others, training and prior experiences) and environmental-related factors (social support and trust) were positively associated with successful farmers’ knowledge sharing behaviour. Furthermore, the findings also indicated that self-efficacy mediates the relationship between individual-related factor (prior experience) and environmental-related factors (social support and trust) on knowledge sharing behaviour. In contrast, it was found that self-efficacy did not mediate the relationship between training (individual-related factor) and knowledge sharing behaviour. It can be concluded that, knowledge sharing behaviour is adopted and practiced by successful farmers. The individual-related factors namely enjoyment in helping others, training and prior experience play a role in knowledge sharing behaviour among successful farmers. Besides that, the environmental-related factors such as social support and trust are vital to promoting knowledge sharing behaviour among successful farmers. Notably, this study found that self-efficacy is a central component in knowledge sharing behaviour among successful farmers. Moreover, this study provides a predictive framework explaining the phenomenon of knowledge sharing behaviour among successful farmers. In spite of that, the present study extends the existing self-efficacy literature and hopes to contribute additional insights to self-efficacy and knowledge sharing studies especially in Malaysia. For the field of agriculture extension, this study will yield additional insights to the relationship between self-efficacy and knowledge sharing behaviour among successful farmers. Furthermore, this study hopes to provide knowledge especially for extension agents and department of agriculture to give attention on individual-related factors and environmental-related factors which could influence self-efficacy and thereby provide practical means to improve knowledge sharing behaviour among farmers in Malaysia.